Review on polyaniline as reductive photocatalyst for the construction of the visible light active heterojunction for the generation of reactive oxygen species. Issue 4 (August 2021) - Ekande, Onkar Sudhir; Kumar, Mathava
Abstract: Polyaniline (PANI), one of the P-type photocatalysts, has high reducing potential and low band energy (Eg ); as a result, it can be activated in visible light. PANI based construction of heterojunctions such as type-II and S-scheme depends on position of lower unoccupied molecular orbital (LUMO), highest occupied molecular orbital (HOMO) and Fermi level (EF ). PANI can be used as a reductive photocatalyst (RP) in the construction of heterojunctions due to high LUMO level. On the other hand, a variety of photocatalysts including metal oxides, bismuth-based, silver-based, metals ferrites and metal organic framework (MOF) can be used as oxidative photocatalyst (OP) in the construction of PANI heterojunctions owing to their low level of valence band (VB). However, relative position of EF of PANI to EF of OP governs the formation of type-II and S-scheme heterojunction. S-scheme heterojunction has advantage over type-II heterojunction due to high redox potential available for the generation of reactive oxygen species (ROS). In this review, the possible OPs for the construction of PANI based S-scheme heterojunction in the generation of ROS were discussed in detail with positions of VB, CB, and EF . Finally, the perspective of PANI heterojunction in terms of detail approach to understand the formation of heterojunction, its stability and application was highlighted. Graphical Abstract: ga1 Highlights: Polyaniline (PANI) is P-type visible light active reductive photocatalyst (RP). PANI's bandgap 2.7 eV and Fermi level (EF ) near HOMO. PANI as RP suitable for type-II heterojunction due to low position of EF . P-type oxidative photocatalyst (OP) is suitable for the construction of S-scheme heterojunction with P-type PANI. PANI has advantage over widely used RP graphitic carbon nitride (g-C3 N4 ).